Teaching Note—Data Science Training for Finance and Risk Analysis - Ashofteh, Afshin (2023)
Ashofteh, A. (2023). Teaching Note—Data Science Training for Finance and Risk Analysis: A Pedagogical Approach with Integrating Online Platforms. In C. P. Kitsos, T. A. Oliveira, F. Pierri, & M. Restaino (Eds.), Statistical Modelling and Risk Analysis: Selected contributions from ICRA9, Perugia, Italy, May 25-27, 2022 (Vol. 430, pp. 17-25). (Springer Proceedings in Mathematics & Statistics). Springer Nature. https://doi.org/10.1007/978-3-031-39864-3_2